Awareness of unclaimed inheritance management: a case study of professionals at UiTM Perak - Mazlan, Ashwadi Ashraf (2025)
This study investigates the awareness of unclaimed inheritance management among professionals at UiTM Perak. The research aims to identify the key factors contributing to unclaimed inheritance and assess the most significant influences on awareness within this group. Factors explored include a lack of awareness and knowledge, the complexity of legal processes, and disputes among heirs. A quantitative research approach was adopted, utilizing questionnaires distributed to 81 respondents, determined based on the Slovin’s formula. The findings reveal that legal complexities and insufficient knowledge are primary barriers to inheritance claims, while awareness of inheritance rights remains limited. The study concludes that educational initiatives and simplified legal processes are crucial for improving inheritance management. This research contributes valuable insights into the issue, providing recommendations for policymakers and legal authorities to encourage proactive inheritance claims and reduce the incidence of unclaimed estates.